Standardization and in-house ELISA setup for helicobacter pylori serologic diagnosis - Shahrestani T (Tehran University Medical Journal, 2001)
Helicobacter pylori (H.pylori) is the most prominent causative agent of gastroduodenal diseases all over the world. Other manifestations such as urticaria and coronary heart diseases, also are suspected to be induced by H.pylori. Non invasive methods are preferred for diagnosis; and ELISA, because of its reliability, speed, sensitivity and specificity is widely preferred as diagnostic tool. Previously we have used IFA, and here, we report an indirect ELISA technique for H.pylori diagnosis. First, 9 strains, of H.pylori isolated from biopsies, were cultured, and the soluble crude antigen was used to coat ELISA plates. Antigen concentration and conjugated antiserum dilution were optimised using checker board method. In this study the gold standard was: rapid urease test, culture and direct smear. Patient serum dillution and the cut-off value was determind, using 22 negative and 30 positive confirmed samples according to ROC curve and the results were compared with a commercial kit. The sensitivity and specificity of this method were 93.2 percent and 95.4 percent respectively. A commercial ELISA Kit, was used and compared simultaneously. The sensitivity and specificity were 87.8 percent and 73 percent respectively. Therefore, regarding the acceptable sensitivity and specificity, ease of work of ELISA, being economical and non-invasive, it can be employed in diagnosis of H.pylori infection and also in epidemiological studies.